Multimédiatisation et événement religieux : le cas de la campagne d’évangélisation l’« Horizon de l’espérance » de Hope Channel Romania (Speranta TV) - Mihaela Alexandra TUDOR (Tic & Société)
Multi-mediatization and religious event: the case of the evangelical campaign "Horizon of Hope" on Hope Channel Romania (Speranta TV) – In this article we will question how the religious media engages with the new Information and Communication Technologies (ICTs) for evangelization by reconstructing neo-protestant Hope Channel Romania’s (Speranta TV) work to implement the evangelical "Horizon of Hope" campaign. Considering that ICTs cannot be regarded yet as stabilized, we suggest that the product of media evangelization created by this religious media is rooted in the logic of cross media convergence between old and new media rather than in a logic of transfer of authority toward the new media.